Stepback Germ / Najihah Abd Latif - Abd Latif, Najihah (2020)
The iNSPIRE is the company that has released a lot of creative and unique products that aim to always give the best products to the customers. This time, our company has successfully released a product named “STEPBACK GERM” that we have produced exclusively to combat germ including bacteria and virus especially in this pandemic era. In addition, our company aim to constantly create new value to produced and invest product to ease our customer. The iNSPIRE is currently planning to larger manufacturing facility in Seremban, Negeri Sembilan and eventually outsource all shipping, packaging and storage to the fulfilment centre in year 2 of operation. The iNSPIRE product is mainly focused on the product that will give ease, convenience and satisfactory to the customer. We have our own designers that has degree in design and technology, and we will seek advisor for our product safety to ensure the safety of our customer. We can expect a lot of advantages because our product is quite unique considering the different feature it serves. Most feature of the hand sanitizer holder in the market nowadays has only either hang on the bag or attach it statically on wall. None of these products has the guaranteed in totally free from germ since consumer either need to open the cap of the hand sanitizer bottle or push the compressor by themselves. We are hundred percent sure that consumer of “STEPBACK GERM” can worry free from any kind of germs cause their hand are not directly touch the hand sanitizer bottle but only push the pedal with their foot. This is our unique and special feature that we can serve specially to the consumer.